PENGEMBANGAN MEDIA INTERAKTIF ROMAKU PADA MATERI SATUAN MASSA DAN KUANTITAS UNTUK MENINGKATKAN HASIL BELAJAR SISWA SD - Orchie Adellia Suci Rahmadhinie; Abdur Rohim (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2026)
Mathematics teaching in elementary schools, particularly regarding the topic of mass and quantity units, still faces challenges in helping students master abstract concepts and unit conversion processes. This situation impacts the lack of conceptual understanding and student participation in the learning process, so clear and engaging learning media are needed to support valuable teaching mechanisms. This study aims to produce ROMAKU (Mass and Quantity Wheel) learning media that can support students when learning the concept of mass and quantity units in an easier, more organized way, and in accordance with student characteristics. This study uses a Research and Development approach with an adaptation of the ASSURE model consisting of six stages: Analyzing Learners, Stating Objectives, Determining Methods, Media, and Materials, Optimizing Media and Materials, Requiring Learning Involvement, and Evaluating and Revising. Study participants consisted of elementary school students studying material on mass and quantity units. Data collection methods included validation sheets from media and material experts, student response questionnaires, and assessment of learning outcomes. Data were analyzed using descriptive quantitative methods with a Likert scale and percentages to assess the validity, practicality, and effectiveness of the media. Research results show that ROMAKU media meets validity standards based on expert assessments with an average percentage of 78% in the high category, is practical based on student responses, and is effective in improving students' conceptual understanding. ROMAKU media is able to help students convert units and solve contextual problems more accurately and independently.